Bridging the Green Gap: An Analysis of the Intention-Behavior Gap in Sustainable Fashion Consumption Among Young Consumers in Nepal - Regmi, Mahima; Aryal, Joshan; Shrestha, Kamala; Rai, Nayandeep; Dhakal, Nisha; Budha, Prem; Lamichhane, Basu Dev (International Journal of Atharva, 2025)
Background: The global fashion industry, a major economic driver, is undergoing a significant transformation shaped by digitalization, evolving consumer demographics, and heightened environmental concerns. While the sector demonstrates resilience, it faces criticism for its environmental impact, including pollution and waste from fast fashion. This has catalyzed a shift towards sustainable practices, such as thrifting, upcycling, and support for eco-friendly brands, driven particularly by younger generations. However, consumer perceptions of these sustainable fashion trends, especially in emerging markets like Nepal, remain an underexplored area in management literature.Objectives: This study aims to assess customer perceptions of sustainable fashion trends, focusing on thrifting preferences, upcycling interest, eco-friendly brand engagement, environmental awareness, and the role of social influence.Methods: A descriptive, quantitative research design was employed. Data were collected from a sample of 204 clothing customers in Nepal using a structured questionnaire featuring a 5-point Likert scale. Participants were selected via convenience sampling and were either current or former students, ensuring familiarity with local trends. Data analysis was conducted using descriptive statistics (mean, standard deviation) to interpret attitudes and behaviors.Findings: The results indicate a strong positive perception and high environmental awareness among consumers. Respondents acknowledged the affordability and uniqueness of thrifting (Mean=3.93) and recognized the effectiveness of upcycling in reducing waste (Mean=3.87). There was a notable willingness to pay more for sustainable brands (Mean=3.79) and a strong consensus on the need for stricter industry regulations (Mean=4.02). However, the actual frequency of thrifting to reduce environmental impact was moderate (Mean=3.10). The primary barriers identified were affordability and accessibility, with the highest agreement (Mean=4.07) on the statement that consumers would buy more sustainable fashion if it were more affordable and widely available.Conclusion: The study concludes that while Nepali consumers, particularly younger demographics, exhibit highly favorable attitudes and strong intentions toward supporting sustainable fashion, a significant intention-behavior gap exists. This gap is predominantly influenced by practical constraints related to cost and availability.Implication: The findings imply that for sustainable fashion to become mainstream, industry stakeholders must strategize to enhance affordability, improve accessibility through wider distribution channels, and intensify educational and promotional efforts. Policymakers can support this transition by implementing regulations that incentivize sustainable production and consumption.